Heterogeneity of reservoir quality and gas accumulation in tight sandstone reservoirs revealed by pore structure characterization and physical simulation. (1st October 2019) - Qiao, Juncheng; Zeng, Jianhui; Jiang, Shu; Feng, Sen; Feng, Xiao; Guo, Zheng; Teng, Jinliang
Highlights: Thin section, SEM and Micro-CT are combined to characterize pore structure. MMPMT, SPFT and MPNT are three major pore configurations in tight gas sandstone. Tight reservoirs are characterized by varied pore structures and gas flow regimes. The gas flow regimes are controlled by the pore structure characteristics. Pore structure variations result in differences in gas migration and accumulation. Abstract: To better understand the quality of the heterogeneous reservoir and gas accumulation in tight sandstone reservoirs, it is necessary to reveal the internal relationship between the reservoir qualities, pore structure and gas migration. In this study, we employ integrated methods including geological data analysis, casting thin section, SEM, XRD and Micro-CT (μ-CT) combined with physical simulation experiments of gas migration for the Upper-Paleozoic Shanxi and Lower Shihezi formations in the Ordos Basin. The results reveal three main pore-throat structures in tight sandstone reservoir in Ordos basin, including the macro-meso pores (>10 μm) with medium throats (1–3 μm) (MMPMT), small pores (2–10 μm) with fine throats (0.5–1 μm) (SPFT) and the micro-nano pores (<2 μm) with nano (<0.5 μm) or no throats (MPNT), and evident variations in pore structures between "sweet spot" and poor reservoir in tight layers. Critical charge pressure square gradient (CCPG), critical migration pressure square gradient (CMPG) and ultimate gas saturation (UGS) are identified to describe gas migration process. "Sweet spot" is characterized by a lower CCPG and CMPG and higher UGS compared with poor reservoir. Comparative analyses indicate the capacity of pore-throat to participate in gas migration is positively correlated with average radii, suggesting meso -small pores (20–2 μm) with medium-fine throats (1–3 μm) are the main pathway for gas migration in tight sandstone reservoirs. The CCPG is determined by the volume fraction and average radii of MMPMT, and CMPG is controlled by the proportion and average radii of SPFT. The configurations of pore structures control the gas accumulation process and affect the degree of accumulation (UGS). Pore structure variation is the primary factor controlling the heterogeneities of reservoir quality and gas accumulation in tight sandstone reservoirs.